2013
DOI: 10.1016/j.ajhg.2013.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Characterization of Shared and Distinct Genetic Components that Influence Blood Lipid Levels in Ethnically Diverse Human Populations

Abstract: Blood lipid concentrations are heritable risk factors associated with atherosclerosis and cardiovascular diseases. Lipid traits exhibit considerable variation among populations of distinct ancestral origin as well as between individuals within a population. We performed association analyses to identify genetic loci influencing lipid concentrations in African American and Hispanic American women in the Women's Health Initiative SNP Health Association Resource. We validated one African-specific high-density lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
110
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(124 citation statements)
references
References 59 publications
(74 reference statements)
14
110
0
Order By: Relevance
“…Previously, we have examined the lipid concentrations in this cohort to characterize overlapping genetic architecture. 21 Here we apply the proposed XP-BLUP method to predict lipid concentrations. For LDL, HDL, and TG, the total estimated heritability on the training set is 0.33, 0.28, and 0.26, respectively.…”
Section: Predicting Genetic Scores For Lipid Concentration In Africanmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have examined the lipid concentrations in this cohort to characterize overlapping genetic architecture. 21 Here we apply the proposed XP-BLUP method to predict lipid concentrations. For LDL, HDL, and TG, the total estimated heritability on the training set is 0.33, 0.28, and 0.26, respectively.…”
Section: Predicting Genetic Scores For Lipid Concentration In Africanmentioning
confidence: 99%
“…Previously we have shown that complex traits genetic architecture overlaps substantially between ethnicities and that harnessing trans-ethnic information leads to substantial improvement in our ability to discover trait loci that are relevant in minority populations. 21,22 Therefore, we reason that trait prediction in minority populations may also benefit from integrating much larger GWAS data generated from populations of European descent. Our proposed approach, termed cross-population BLUP (XP-BLUP), is a multiple-component LMM model designed specifically to address the need for efficient prediction in minority populations.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier genetic studies linked CD36 to fasting lipids (21, 48), MetS (22,(49)(50)(51), and stroke risk (44). However, information related to the role of the gene in postprandial lipid metabolism, which plays an important role in etiology of MetS and cardiovascular disease, remains limited.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic variants generally appear to exert similar effects across ethnicities if tested in a suffi ciently powered cohort, but differences in allele frequency and regional linkage disequilibrium (LD) between ethnicities allows for the identifi cation of novel contributors to lipid metabolism (3)(4)(5). While efforts to identify additional variants associated with blood lipids in African-American populations have been successful ( 3,(6)(7)(8), the identifi cation of novel genetic loci in nonEuropean populations has been hampered by inadequate power due to limited sample size and genotyping platform designs made for optimal SNP coverage of European populations ( 3,9 ).…”
Section: African American Meta-analysismentioning
confidence: 99%
“…There was no sample overlap between the WHI and WHI-SHARe genotyping initiatives. Further details of the populations, genotyping, and quality control analysis have been published elsewhere ( 6,8 ). All participants provided informed written consent.…”
mentioning
confidence: 99%